2021
DOI: 10.5194/tc-15-3897-2021
|View full text |Cite
|
Sign up to set email alerts
|

MOSAiC drift expedition from October 2019 to July 2020: sea ice conditions from space and comparison with previous years

Abstract: Abstract. We combine satellite data products to provide a first and general overview of the physical sea ice conditions along the drift of the international Multidisciplinary drifting Observatory for the Study of Arctic Climate (MOSAiC) expedition and a comparison with previous years (2005–2006 to 2018–2019). We find that the MOSAiC drift was around 20 % faster than the climatological mean drift, as a consequence of large-scale low-pressure anomalies prevailing around the Barents–Kara–Laptev sea region between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…The measurement program was part of the Multidisciplinary Drifting Observatory for the Study of Arctic Climate (MOSAiC) expedition ( https://mosaic-expedition.org ), which took place in the Arctic from October 2019 to October 2020 and was divided into five legs 1 . RV Polarstern 2 was drifting attached to an ice floe along the transpolar drift from about 85 N north of the Laptev Sea towards Fram Strait between Svalbard and Greenland 1 , 3 . To study the Arctic climate, a research camp, called Central Observatory (CO), was installed on a second-year ice floe that survived the summer and originated from the Laptev Sea 4 .…”
Section: Background and Summarymentioning
confidence: 99%
“…The measurement program was part of the Multidisciplinary Drifting Observatory for the Study of Arctic Climate (MOSAiC) expedition ( https://mosaic-expedition.org ), which took place in the Arctic from October 2019 to October 2020 and was divided into five legs 1 . RV Polarstern 2 was drifting attached to an ice floe along the transpolar drift from about 85 N north of the Laptev Sea towards Fram Strait between Svalbard and Greenland 1 , 3 . To study the Arctic climate, a research camp, called Central Observatory (CO), was installed on a second-year ice floe that survived the summer and originated from the Laptev Sea 4 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Changes in sea ice drift, thickness and concentration are associated with changes in sea ice deformation. The deformation rate of pack ice is a key parameter determining the formation of sea ice linear kinematic features like leads (e.g., Kwok, 2001;Wang et al, 2016b;Bouchat and Tremblay, 2017;Mohammadi-Aragh et al, 2018Hutter et al, 2019;Hutter and Losch, 2020;Rampal et al, 2019). The model resolution we used cannot realistically represent these features due to their narrowness in reality.…”
Section: Impact On Sea Ice Deformationmentioning
confidence: 99%
“…Then, it increased from March 2020 and this seemed partly related to the complex ice deformation caused by external forcing. It was reported that stormy conditions at the MO-SAiC floe were encountered in mid-November, late February, mid-April, and late May [30]. Figure 9 shows the monthly distribution of speed bias to investigate seasonal dependencies.…”
Section: Discussionmentioning
confidence: 99%
“…Then, it increased from March 2020 and this seemed partly related to the complex ice deformation caused by external forcing. It was reported that stormy conditions at the MOSAiC floe were encountered in mid-November, late February, mid-April, and late May [30]. The use of a cross-sensor resulted in a good performance; however, a higher MCC threshold was required to achieve a similar level to the single-sensor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation